2018
DOI: 10.1074/jbc.ra118.002122
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heat-induced protein aggregation in human mitochondria

Abstract: Proteins in mammalian cells exhibit optimal stability at physiological temperatures, and even small temperature variations may cause unfolding and nonspecific aggregation. Because this process leads to a loss of function of the affected polypeptides and to cytotoxic stress, formation of protein aggregates has been recognized as a major pathogenic factor in human diseases. In this study, we determined the impact of physiological heat stress on mitochondria isolated from HeLa cells. We found that the heat-stress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 59 publications
4
59
1
Order By: Relevance
“…Shekar et al [ 69 ] found that under conditions of heart failure, which is associated with reduced mitochondrial function, the turnover rate of several proteins involved in fatty acid oxidation, electron transport chain and ATP synthesis was increased. On the other hand, even mild heat stress causes reduced rates of mitochondrial protein synthesis, which is correlated with aggregation of the essential mitochondrial translation factor Tufm [ 70 ]. This aggregation and inactivation was interpreted as a protective response—by reducing mitochondrial protein synthesis, the accumulation of other aggregated mitochondrially synthesized proteins under stress conditions is avoided and this makes the point that changes in rates of synthesis or abundance of some proteins as a result of stress or ageing are not necessarily indicative of degenerative change.…”
Section: Regulation Of Mitochondrial Gene Expression and Age-relatmentioning
confidence: 99%
“…Shekar et al [ 69 ] found that under conditions of heart failure, which is associated with reduced mitochondrial function, the turnover rate of several proteins involved in fatty acid oxidation, electron transport chain and ATP synthesis was increased. On the other hand, even mild heat stress causes reduced rates of mitochondrial protein synthesis, which is correlated with aggregation of the essential mitochondrial translation factor Tufm [ 70 ]. This aggregation and inactivation was interpreted as a protective response—by reducing mitochondrial protein synthesis, the accumulation of other aggregated mitochondrially synthesized proteins under stress conditions is avoided and this makes the point that changes in rates of synthesis or abundance of some proteins as a result of stress or ageing are not necessarily indicative of degenerative change.…”
Section: Regulation Of Mitochondrial Gene Expression and Age-relatmentioning
confidence: 99%
“…This process leads to a loss of function of the affected polypeptides and to cytotoxic stress, which in turn causes pathological events. Short‐term high environmental temperatures only marginally affect the overall solubility of endogenous proteins; however, a small subset of polypeptides exhibited a high sensitivity to HS (Wilkening, Rüb, Sylvester, & Voos, ). In particular, the mitochondrial translation elongation factor Tu (Tufm), a protein essential for organelle protein biosynthesis, is highly aggregation‐prone and loses its solubility even under mild HS conditions.…”
Section: Subcellular Alterationsmentioning
confidence: 99%
“…As noted above, the ROS-induced protein damage may also be efficiently dealt with by the mitochondrial proteases, reducing the risk of aggregate formation. Also, in mammalian mitochondria, it was shown that elevated temperatures generated protein aggregation, although many proteins were remarkably resilient against this type of stress conditions [44]. Interestingly, one of the most aggregation-prone mitochondrial proteins was the translation factor Tu (encoded by TUFM), suggesting that a shutdown of mitochondrial translation under stress conditions is a major protective mechanism to prevent accumulation of damaged proteins.…”
Section: Prevention Of Aggregationmentioning
confidence: 99%